Desenvolvimento de um novo complexo macrocíclico do sistema cobalto cyclam - Maia, Danielle de Oliveira (2011)
In this work were synthesized and studied the spectroscopic and electrochemical characteristics of the coordination compounds trans-[Co (cyclam)Cl2]Cl, trans- Na[Co(cyclam)(tios)2], trans-[Co(en)2Cl2]Cl and trans-Na[Co(en)2(tios)2], where tios = thiosulfate and en = ethylenediamine. The compounds were characterized by: Elemental Analysis (CHN), Absorption Spectroscopy in the Infrared (IR), Uv-Visible Absorption Spectroscopy, Luminescence Spectroscopy and Electrochemistry (cyclic voltammetry). Elemental Analysis (CHN) suggests the following structures for the complex: trans- [Co(cyclam)Cl2]Cl.6H2O and trans-Na[Co(cyclam)(tios)2].7H2O. The electrochemical analysis, when compared the cathodic potential (Ec) processes of the complexes trans- [Co(cyclam)Cl2]Cl and trans-[Co(en)2Cl2]Cl, indicated a more negative value (-655 mV) for the second complex, suggesting a greater electron donation to the metal center in this complex which can be attributed to a greater proximity of the nitrogen atoms of ethylenediamine in relation to metal-nitrogen cyclam. Due to the effect of setting macrocyclic ring to the metal center, the metal-nitrogen bound in the cyclam are not as close as the ethylenediamine, this fact became these two ligands different. Similar behavior is also observed for complexes in which the chlorides are replaced by thiosulfate ligand, trans-Na[Co(en)2(tios)2] (-640 mV) and trans-Na[Co(cyclam)(tios)2] (-376 mV). In absorption spectroscopy in the UV-visible, there is the band of charge transfer LMCT (ligand p d* the metal) in the trans-Na[Co(cyclam)(tios)2] (350 nm, p tios  d* Co3+) and in the trans-Na[Co(en)2(tios)2] (333 nm, p tios d* Co3+), that present higher wavelength compared to complex precursor trans- [Co(cyclam)Cl2]Cl (318 nm, pCl  d* Co3+), indicating a facility of electron density transfer for the metal in the complex with the thiosulfate ligand. The infrared analysis showed the coordination of the thiosulfate ligand to the metal by bands in the region (620-635 cm-1), features that prove the monodentate coordination via the sulfur atom. The νN-H bands of the complexes with ethylenediamine are (3283 and 3267 cm-1) and the complex with cyclam bands are (3213 and 3133 cm-1). The luminescence spectrum of the trans-Na[Co(cyclam)(tios)2] present charge transfer band at 397 nm and bands dd at 438, 450, 467, 481 and 492 nm.